Thermomechanical behavior of SBR reinforced with nanotubes functionalized with polyvinylpyridine - de Falco, Alejandro Diego (2012)
The mechanical and thermal behavior of composites consisting on a styrene-butadiene rubber (SBR) matrix with a sulphur/accelerator system and multiwalled carbon nanotubes functionalized with poly-4-vinylpyridine (MWCNT-PVP) as reinforcement, were studied. The materials were tested with stress-strain tensile tests, DMTA and DSC for thermal properties. A strong increase in the plastic behavior with slight decrease of its elastic Modulus and Tg led to unexpected results.